Financial Resource Development Strategy at the Food Barn of Gondowangi Village, Wagir District, Malang Regency - Nurjaya, Grasiani Saputri; Cakti Indra Gunawan; Imam Hidayat (IRDH International Journal of Social Sciences & Humanities, 2025)
The purpose of this research is to identify strategies for developing financial resources in the Food Barn of Gondowangi Village, Wagir District, Malang Regency. This study employed a qualitative method with data collection techniques including interviews, observations, and documentation. Data were analyzed descriptively using a SWOT approach. The results show that strategies implemented to enhance financial resources include capital management through Village Fund Budgeting (ADD), utilization of human resources (HR) for financial report preparation, transparent and comprehensive financial reporting, and revenue enhancement strategies through cooperation with grocery stores and rice milling services. The findings highlight the importance of transparent financial reporting, HR capacity building, and business diversification of BUMDes to strengthen village food security.